Penerapan Restorative Justice oleh Pengadilan Negeri Medan untuk Mewujudkan Kepastian Hukum dalam Penyelesaian Tindak Pidana - Meliala, Nugraha Manuella; Ismaidar; Sahlepi, Muhammad Arif (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
This research aims to evaluate the effectiveness of the implementation of restorative justice by the District Court of Medan in achieving legal certainty for all parties involved in the legal process. The research method used is normative juridical legal research, focusing on written regulations and other legal materials. Data collection is conducted through literature review to explore concepts, theories, or opinions regarding Legal Certainty in the Implementation of Restorative Justice. The analysis is qualitative, explaining the relationship between types of data, selection, and data processing to be systematically outlined. The conclusion of the analysis will include answers to the issues raised and evidence of the truth or falsity of the hypotheses proposed. The results of the research indicate that the Indonesian Criminal Justice System has undergone renewal with the introduction of the concept of restorative justice. This involves perpetrators, victims, and other stakeholders in seeking fair solutions and peace after criminal events. The Public Prosecutor's Office plays a crucial role in prosecution, and the principle of "enn en ondeelbaar" asserts its functional unity. Restorative Justice has been regulated in laws and regulations, providing opportunities for victims and perpetrators to participate in peaceful case resolution. Restorative Justice offers an alternative to criminal case resolution outside the courtroom, focusing on restoration and reconciliation. In the District Attorney's Office of Medan, the process requires detailed administration. The regulation of victim protection in criminal law is stipulated in Indonesian positive law. Restorative Justice is applied in the general court environment with the aim of creating legal certainty and justice for all parties involved. Legal certainty in the application of Restorative Justice allows for various alternative handling of criminal offenses outside the courtroom, such as out-of-court settlements. This can reduce case backlog and high costs, as well as shorten the resolution process compared to litigation. Restorative Justice also prioritizes substantive justice with a focus on the interests of victims and restoring conditions to pre-criminal levels.